2022
DOI: 10.1108/ijrdm-05-2021-0222
|View full text |Cite
|
Sign up to set email alerts
|

I “showroom” but “webroom” too: investigating cross-shopping behaviour in a developing nation

Abstract: PurposeThe concepts of showrooming and webrooming have been well researched but majorly from the marketing/economic perspectives. The present study explores the socio-psychological motivations and different types of satisfaction derived from “cross-shopping” behaviour namely, showrooming and webrooming in a developing nation.Design/methodology/approachThe study is exploratory and is conducted using an interpretive approach. The researchers conducted 52 in-depth interviews and the collected data were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…While the pandemic has accelerated the adoption of e‐commerce, showrooming, webrooming, and omnichannel studies are research areas that have interested researchers for several years. These studies include exploring the drivers of consumer adoption of e‐commerce (Zerbini et al, 2022), investigating online experiences shaping webrooming behavior (Schiessl et al, 2023), and examining the cross‐shopping behavior, specifically showrooming and webrooming in a developing nation context (Roy et al, 2022).…”
Section: Science Mapping Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the pandemic has accelerated the adoption of e‐commerce, showrooming, webrooming, and omnichannel studies are research areas that have interested researchers for several years. These studies include exploring the drivers of consumer adoption of e‐commerce (Zerbini et al, 2022), investigating online experiences shaping webrooming behavior (Schiessl et al, 2023), and examining the cross‐shopping behavior, specifically showrooming and webrooming in a developing nation context (Roy et al, 2022).…”
Section: Science Mapping Results and Discussionmentioning
confidence: 99%
“…These studies include exploring the drivers of consumer adoption of e-commerce (Zerbini et al, 2022), investigating online experiences shaping webrooming behavior (Schiessl et al, 2023), and examining the cross-shopping behavior, specifically showrooming and webrooming in a developing nation context (Roy et al, 2022).…”
Section: Pandemic Studies (Ts3 Period)mentioning
confidence: 99%
“…Interestingly, recent research has relied upon “Integrated store service quality” to demonstrate the different engagement behaviors of the omnichannel shoppers (Natarajan and Ramanan, 2023) and their online, offline and social media word of mouth behaviors (Natarajan and Veera Raghavan, 2023b) but not on the behaviors that bring in revenue to store like cross-buying behaviors or customers’ willingness to pay more. Parallelly, recent omnichannel literature has focused on webrooming phenomena to decode the antecedents (Aw, 2019) and factors affecting webrooming intentions (Shankar and Jain, 2021), highlighting its benefits to customers in terms of overall satisfaction (Roy, 2022). They have demonstrated how product characteristics, consumer traits and channel-related factors affect customer webrooming intentions (Aw, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, findings from prior studies revealed that the decision to webroom can be determined by different economic and non-economic motivations (e.g. efficiency shopping, deprivation-curiosity interest and joy of discovery) (Aw, 2019;Roy et al, 2022). The latest research has started to explore the experience and outcomes of webrooming.…”
Section: Literature Review and Conceptual Development 21 Webroomingmentioning
confidence: 99%